Analysis of Burnout, Employee Engagement and Compensation on Turnover Intention of Shopee Express Hub Surabaya Couriers - Syanindita Aurelya Ayu Widya Savitri; Gendut Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2023)
Companies often encounter the prevalent occurrence of turnover intention. Shopee Express Hub Surabaya is one of many companies facing turnover intention. This can be caused by various factors, including burnout experienced by couriers, employee engagement owned by couriers and compensation obtained by couriers. This study aims to analyze the effect of Burnout, Employee Engagement and Compensation on Turnover Intention of Shopee Express Hub Surabaya couriers. The study's participants were the couriers at the Shopee Express Hub in Surabaya. Purposive sampling was utilized in the sampling procedure, and 65 respondents were obtained overall. The number of samples was calculated using the Slovin method. A questionnaire was used to gather the data, and after that, Partial Least Square (PLS) software was used to analyze the data using various data analysis techniques.According to the research's results, employee engagement has a considerable negative influence on turnover intention, whereas compensation has a non-significant negative impact. Burnout also has a big positive impact on turnover intention.